Controllability of second-order semilinear infinite-dimensional dynamical systems - Klamka, Jerzy (1944- ) (Zielona Góra: Uniwersytet Zielonogórski)
In the paper, the approximate controllability of semilinear abstract second-order infinite-dimensional dynamical systems is considered. It is proved by using the frequency-domain and functional-analysis methods that the approximate controllability of second-order semilinear dynamical system can be verified by the approximate controllability conditions for a simplified suitably-defined first-order linear dynamical system.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka